The relationship between servant leadership, emotional intelligence, trust in the immediate supervisor and meaning in life : an exploratory study - Van Staden, Marieta (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MA (Industrial Psychology))--University of Stellenbosch, 2007.